Neutrophil extracellular traps in central nervous system pathologies: A mini review - Shafqat, Areez; Noor Eddin, Ahmed; Adi, Ghaith; Al-Rimawi, Mohammed; Abdul Rab, Saleha; Abu-Shaar, Mylia; Adi, Kareem; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Medicine, 2023)
Neutrophils are the first cells to be recruited to sites of acute inflammation and contribute to host defense through phagocytosis, degranulation and neutrophil extracellular traps (NETs). Neutrophils are rarely found in the brain because of the highly selective blood-brain barrier (BBB). However, several diseases disrupt the BBB and cause neuroinflammation. In this regard, neutrophils and NETs have been visualized in the brain after various insults, including traumatic (traumatic brain injury and spinal cord injury), infectious (bacterial meningitis), vascular (ischemic stroke), autoimmune (systemic lupus erythematosus), neurodegenerative (multiple sclerosis and Alzheimer’s disease), and neoplastic (glioma) causes. Significantly, preventing neutrophil trafficking into the central nervous system or NET production in these diseases alleviates brain pathology and improves neurocognitive outcomes. This review summarizes the major studies on the contribution of NETs to central nervous system (CNS) disorders.